A Systematic Mapping Study of Emotion Analysis in Arabic Language (Journal of Academic Research, 2023)
In this study, we address the problem of emotion analysis in Arabic text by reviewing the current studies on the topic between the years 2013- 2023.The standard systematic mapping study method has been employed collecting 62 studies on Arabic emotion text research, including 31 articles from SCOPUS, and 31 from Google Scholar.The results of the review indicates that the largest number of research was conducted and published in 2023.  31 journals published articles in the area of Arabic Emotion Detection, and the journal that published the most articles is Applied Science (MDPI). The statistical approach using different supervised machine learning algorithms has been the most popular approach for Arabic Emotion Analysis for the past ten years, followed by the deep learning algorithms. There are only two studies that have used lexical-based techniques and the hybrid approach. The data sets collected from social media platforms (Twitter and Facebook) are the most widely used in the Arabic text emotion analysis, especially Twitter. Lastly, the number of type of emotions used in previous studies to detect Arabic emotion amounted to 26 emotions, where the most common emotion types recognized were: sadness, anger, fear, joy, surprise, disgust, and love.